Cancer in Pregnancy. Issue 6 (22nd August 2019) - Eastwood‐Wilshere, Naomi; Turner, Jessica; Oliveira, Niara; Morton, Adam
Abstract: Cancer in pregnancy may be increasing in incidence with advancing maternal age and higher rates of obesity. The diagnosis of cancer in pregnancy provokes complex management issues balancing short‐ and long‐term risks for both mother and baby. Every case needs to be individualized, with a multidisciplinary team of midwives, obstetricians, oncologists, surgeons, radiation oncologists, and neonatologists assisting the family to make informed decisions regarding the best treatment course for the mother and baby. The present article reviews the evidence regarding the safety of diagnostic imaging, procedures and treatment modalities for cancer for the pregnant woman and fetus. The efficacy of novel anticancer therapies highlight the need for International Registries to accumulate safety data for these agents in pregnancy as expeditiously as possible.